In Vitro Activity of the New Oxazolidinone AZD2563 against Enterococci - Eliopoulos, G. M. (American Society for Microbiology, 2002)
The activity of a new oxazolidinone antimicrobial, AZD2563, was assessed against >500 clinical isolates of enterococci representing six species. All isolates, including those resistant to other antibiotic classes, were inhibited by AZD2563 at concentrations ≤2 μg/ml, except for four strains resistant to linezolid. In most cases, AZD2563 was twofold more active than linezolid against enterococci.